(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article explores the importance and impact of leveraging visual tools in the development of the professional competence of educators. In the dynamic landscape of education, pedagogues play a pivotal role in shaping the minds and futures of their students. The development of professional competence among educators is a continuous and evolving process. One powerful avenue for enhancing pedagogical skills is through the strategic integration of visual means.